2015
DOI: 10.1590/1809-4430-eng.agric.v35n6p979-989/2015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of piglets’ rectal temperature and respiratory rate through skin surface temperature under climatic chamber conditions

Abstract: ABSTRACT:In animal farming, an automatic and precise control of environmental conditions needs information from variables derived from the animals themselves, i.e. they act as biosensors. Rectal temperature (RT) and respiratory rate (RR) are good indicators of thermoregulation in pigs. Since there is a growing concern on animal welfare, the search for alternatives to measure RT has become even more necessary. This research aimed to identify the most adequate body surface areas, on nursery-phase pigs, to take t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…These errors are lower than those previously reported from either statistical or mechanistic models. Mostaço et al (2015) predicted rectal temperatures of pigs with 2.5% error using multiple linear regression for air enthalpy and tympanic temperature (known to be correlated with internal body temperature; Korthals et al, 1995). Costa et al (2010) predicted surface temperature of piglets with 5.5% error using a linear regression model.…”
Section: Training and Testing Machine Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These errors are lower than those previously reported from either statistical or mechanistic models. Mostaço et al (2015) predicted rectal temperatures of pigs with 2.5% error using multiple linear regression for air enthalpy and tympanic temperature (known to be correlated with internal body temperature; Korthals et al, 1995). Costa et al (2010) predicted surface temperature of piglets with 5.5% error using a linear regression model.…”
Section: Training and Testing Machine Learning Modelsmentioning
confidence: 99%
“…Empirical models are data-based and usually assume a linear relationship between predictor variables (e.g., air temperature) and the response variable (e.g., internal-body temperature). These relationships are chosen by the researcher and has a considerable impact on the accuracy of the model (Mostaço et al, 2015;Pathak et al, 2009;Ramirez, 2017;Soerensen and Pedersen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to apply IRT to fever diagnosis, modeling the correlation between skin temperature and internal temperature becomes inevitable. Previous research has shown that the "thermal windows" of pigs, such as the sulcus auriculae posterior [15], eye [16], and vulva [11,12], are highly correlated with the surface temperature and internal temperature of swine. Such regions are usually referred to as regions of interest (ROI).…”
Section: Introductionmentioning
confidence: 99%
“…Infrared cameras are more software intensive than infrared thermometers and can be used for monitoring large areas (Sellier et al, 2014), which allow for a greater representation of the T S of the entire animal or at specific sites as desired by the researcher. An alternative to infrared technology that may be more invasive are contact sensors affixed to the skin (Teunissen et al, 2011;Mostaço et al, 2015). Contact sensors are more accurate than infrared technology and provide continuous automated measurements, but potential issues precluding their use may include battery life and long-term adhesion to the skin (Mostaço et al, 2015), and destruction or loss of the devices in group-housed animals.…”
Section: Skin Temperaturementioning
confidence: 99%
“…An alternative to infrared technology that may be more invasive are contact sensors affixed to the skin (Teunissen et al, 2011;Mostaço et al, 2015). Contact sensors are more accurate than infrared technology and provide continuous automated measurements, but potential issues precluding their use may include battery life and long-term adhesion to the skin (Mostaço et al, 2015), and destruction or loss of the devices in group-housed animals. Therefore, researchers should assess both types of technology and determine which one best fits their requirements in a particular environment or research setting.…”
Section: Skin Temperaturementioning
confidence: 99%